Решение задачи о неосесимметричных колебаниях полых пьезокерамических цилиндров конечной длины - Лоза, И.А. (Доповіді НАН України, 2010)
Розглядається задача про власнi неосесиметричнi коливання порожнистих п’єзокерамiчних цилiндрiв, поляризованих у радiальному напрямi. Пiсля роздiлення змiнних i подання компонентiв вектора перемiщень у виглядi стоячих хвиль у напрямку кругової координати вихiдна тривимiрна задача зводиться до двовимiрної. Застосування методу сплайн-колокацiй за поздовжньою координатою дозволяє дану двовимiрну задачу звести до граничної задачi в звичайних диференцiальних рiвняннях. Отримана задача розв’язується стiйким методом дискретної ортогоналiзацiї у поєднаннi з методом покрокового пошуку. Наведено результати чисельного аналiзу частот власних коливань цилiндра у широкому спектрi змiни геометричних характеристик. The problem on non-axisymmetric vibrations of a hollow piezoceramic cylinder polarized in the radial direction is considered. The initial three-dimensional problem is reduced to a two-dimensional one by the separation of variables and the presentation of the displacement vector components as standing waves in the circumferential direction. Using the method of spline-collocations on the longitudinal coordinate allows us to reduce the two-dimensional boundary-valued problem to that with ordinary differential equations. The problem obtained is solved by the stable discrete orthogonalization coupled with the step-by-step search method. The numerical results are presented for natural frequencies of vibrations in a wide range of the cylinder geometric characteristics.